2017
DOI: 10.1126/sciadv.1700321
|View full text |Cite
|
Sign up to set email alerts
|

Assembling oppositely charged lock and key responsive colloids: A mesoscale analog of adaptive chemistry

Abstract: Oppositely charged thermoresponsive particles with complementary geometries are assembled into adaptive colloidal molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 37 publications
1
49
0
Order By: Relevance
“…1b (right) for R K o 0.5375R L . These analytic results are in agreement with simulations using lock-and key-particles with hard body conditions, 32 which is illustrated for two cases in Fig. 1.…”
Section: Entropic Contributionsupporting
confidence: 85%
See 1 more Smart Citation
“…1b (right) for R K o 0.5375R L . These analytic results are in agreement with simulations using lock-and key-particles with hard body conditions, 32 which is illustrated for two cases in Fig. 1.…”
Section: Entropic Contributionsupporting
confidence: 85%
“…31 Recently, it has been demonstrated that thermoresponsive microgel-based lock-and key-particles may interact to form defined colloidal molecules simply by considering them as oppositely charged building blocks. 32 Other studies also point to electrostatics being an important factor where assembly between lock-and keyparticles is concerned. 33 By taking advantage of the fact that both the geometrical parameters and interactions could be tuned with temperature, the valence of the clusters can be controlled from a tetravalent ''methane''-to a divalent ''carbon dioxide''-like configuration.…”
Section: Introductionmentioning
confidence: 99%
“…8 The initial work had primarily focused on the use of hard sphere-like colloids, which was instrumental in experimentally demonstrating the existence of an entropically driven crystallization in a purely hard spherelike system, 7 and in developing a new research thrust focusing on glass transition, dynamic arrest and jamming. [35][36][37][38] Subsequently the field has seen a dramatic increase in the complexity of colloids and colloidal interactions, and there were in particular four developments that are especially important for the topic of this article: the importance of short-range attractions on colloid phase behavior; 8,13,14,39 equilibrium cluster formation in systems with mixed potentials, combining a long-range soft repulsion and a short-range attraction; 25,[40][41][42] the development of anisotropic particles, [43][44][45][46][47][48] and finally the dramatic consequences of patchy interactions on phase behavior, self-assembly and colloid dynamics. 31,43,45,[49][50][51] As we will see below, these recent developments are also of prime importance for our understanding of protein solutions, and we therefore briefly summarize the most important features.…”
Section: Current Trends In Colloid Sciencefrom Hard Spheres To Anisotmentioning
confidence: 99%
“…In this context, the internal dynamics in nature are a source of inspiration to form controllable and reversible assembly structures using articial building blocks such as colloidal particles with a rich functionality of the individual particles, and can serve the development of novel materials for the application in micromotors, 1-3 photonics/ plasmonics, 4 drug delivery, 5 catalysis, 6 solar cells, 7 sensors, 8 and electronic ink technology. 9 The assembly process can be triggered, on the one hand, by the intrinsic properties of the colloids such as charges, [10][11][12][13][14] amphiphilicity 15 and depletion interactions 16,17 forming supraparticular assemblies. On the other hand, assembly can be provoked eld-assisted by an electric, 1,18-20 magnetic [21][22][23][24][25] or ow eld.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are only few examples of reversible selfassembly of non-Janus 12,14,27,[33][34][35][36][37][38][39][40][41][42][43][44] and Janus particles 15,25,34,45 discussed in the literature. The reported colloidal building blocks exhibit either a purely so (organic), 14 purely hard (inorganic), or hybrid (so/hard) character. 43 An example for dynamic assemblies of so colloids was shown by Crassous and coworkers who employed oppositely charged temperatureresponsive core-shell particles with complementary shapes for a reversible lock-and-key assembly mechanism.…”
Section: Introductionmentioning
confidence: 99%